Friendship of e e and π \pi

True or false:

π \pi is a transcendental number but e e is not transcendental.

True False

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

André Hucek
Oct 7, 2017

A number which doesn't satisfy any algebraic equation of undivided (solid) rational coefficients is called transcendental.

I will here prove that e e is transcendental:

I'll start from the formula achieved from integration by parts:

0 r e x f ( x ) d x = [ e x f ( x ) ] 0 r + 0 r e x f ( x ) d x \large\int^{r}_{0}e^{-x}f(x)dx = - [e^{-x}f(x)]^r_0 + \int^{r}_{0}e^{-x}f'(x) dx .

If f ( x ) f(x) is a polynomial of x N x N th degree, we get:

F ( x ) = f ( x ) + f ( x ) + f ( x ) + . . . + f N ( x ) F(x) = f(x)+f'(x)+f''(x)+...+f^{N}(x)

0 r e x f ( x ) d x = F ( 0 ) F ( r ) e r \int^{r}_{0}e^{-x}f(x) dx = F(0) - F(r) e^{-r}

From which:

F ( r ) = F ( 0 ) e r e r 0 r e x f ( x ) F(r) = F(0) e^r - e^r \int^{r}_{0} e^{-x} f(x)

Let's now suppose that e e satisfies an algebraic equation: a 0 e n + a 1 e n 1 + . . . + a n 1 e + a n = 0 a_0 e^n + a_1e^{n-1} +...+ a_{n-1}e + a_n = 0 ,

and let's define for f ( x ) f(x) : f ( x ) = 1 ( p 1 ) ! x p 1 ( 1 x ) p ( 2 x ) p . . . ( n x ) p f(x) = \frac{1}{(p-1)!} x^{p-1} (1-x)^p (2-x)^p...(n-x)^p .

So the equation: F ( r ) = F ( 0 ) e r e r 0 r e x f ( x ) F(r) = F(0) e^r - e^r \int^{r}_{0} e^{-x} f(x) implies, that if r = n r = n , so r = n 1 , r = n 2 , . . . r = 0 r = n-1, r = n-2 ,... r = 0 there are totally n + 1 n+1 equations, which we multiply by a 0 , a 1 , a 2 , . . . , a n a_0, a_1, a_2, ..., a_n and sum together.

If we then substitute the F ( 0 ) F(0) on the right hand, we get:

a 0 F ( n ) + a 1 F ( n 1 ) + . . . + a n 1 F ( 1 ) + a n F ( 0 ) = k = 0 n a k e n k 0 n k e x f ( x ) d x a_0 F(n) + a_1 F(n-1) +...+a_{n-1} F(1) + a_n F(0) = - \sum^{n}_{k=0} a_k e^{n-k} \int^{n-k}_{0} e^{-x} f(x) dx .

Which is impossible for e e , as:

If we plug in f ( x ) f(x) any of the numbers 1 , 2 , . . . , n 1, 2, ...,n we get either 0 0 or an integer divisible by p p . So for x = 0 x = 0 , we get f ( 0 ) = f ( 0 ) = f ( 0 ) = . . . f ( p 2 ) ( 0 ) = 0 f(0) = f'(0) = f''(0) = ...f^{(p-2)}(0) = 0 ;

Further f ( p 1 ) ( 0 ) = ( 1 × 2 × 3... × n ) p f^{(p-1)}(0) = (1 \times 2 \times 3 ...\times n)^p ; f ( p ) ( 0 ) ; f ( p + 1 ) ( 0 ) f^{(p)}(0); f^{(p+1)}(0) are integers, which again are divisible by p p . So if p p is a prime number p > n p>n ,

F ( 0 ) = n Z F(0) = n \in \mathbb Z not divisible by p p .

Let also p > a n p> \vert a_n \vert , then the polynomial:

a 0 F ( n ) + a 1 F ( n 1 ) + . . . + a n 1 F ( 1 ) + a n F ( 0 ) a_0 F(n) + a_1 F(n-1) +...+ a_{n-1} F(1) + a_n F(0)

is a whole number not divisible by p p .

From k = 0 n a k e n k 0 n k e x f ( x ) d x - \sum^{n}_{k=0} a_k e^{n-k} \int^{n-k}_{0} e^{-x} f(x) dx we assume from the Intermediate value theorem, that:

0 n k f ( x ) e x d x = f ( ξ ) ( 1 e n + k ) < f ( ξ ) < n ( n + 1 ) p 1 ( p 1 ) ! \vert \int^{n-k}_{0} f(x) e^{-x} dx \vert = \vert f(\xi) \vert (1 - e^{-n+k}) < \vert f(\xi) \vert < \frac{n^{(n+1)p-1}}{(p-1)!} .

So let

M = a 0 e n + a 1 e n 1 + a 2 e n 2 + . . . + a n M = \vert a_0 \vert e^n + \vert a_1 \vert e^{n-1} + \vert a_2 \vert e^{n-2} +...+ \vert a_n \vert , then

k = 0 n a k e n k 0 n k e x f ( x ) d x < M n ( n + 1 ) p 1 ( p 1 ) ! - \sum^{n}_{k=0} a_k e^{n-k} \int^{n-k}_{0} e^{-x} f(x) dx < M \frac{n^{(n+1)p-1}}{(p-1)!} in absolute value.

However the prime number p p is defined only by conditions p > a n , p > n p > \vert a_n \vert, p > n , so it can be of any size. So if they are large enough, the expression: M n ( n + 1 ) p 1 ( p 1 ) ! M \frac{n^{(n+1)p-1}}{(p-1)!} becomes arbitrarily small, for example we could choose a p p large enough, so that the expression is smaller than 1 1 , then the equation

a 0 F ( n ) + a 1 F ( n 1 ) + . . . + a n 1 F ( 1 ) + a n F ( 0 ) = k = 0 n a k e n k 0 n k e x f ( x ) d x \vert a_0 F(n) + a_1 F(n-1) +...+a_{n-1} F(1) + a_n F(0) = - \sum^{n}_{k=0} a_k e^{n-k} \int^{n-k}_{0} e^{-x} f(x) dx\ \vert must equal at least 1 1 in it's absolute value equal to a number < 1 <1 , which is impossible since an absolute value can't be negative. That means that e e doesn't satisfy the equation a 0 e n + a 1 e n 1 + . . . + a n 1 e + a n = 0 a_0 e^n + a_1e^{n-1} +...+ a_{n-1}e + a_n = 0 , which means, that e e is transcendental \boxed{\text{is transcendental}} .

Therefore the answer to the claiming is false \boxed{\text{false} }

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...